The Role And Importance Of Creative-Communicative Skills In The Formation Of Professionalism In Higher Education - Khaitova Yulduz Saitovna (Genius Publishing Group, 2022)
This Article Presents An Analysis Of The Role And Importance Of CreativeCommunicative Skills In The Formation Of Professionalism In Higher Education. In Addition, The Problems On The Development Of Creative And Communicative Abilities Of The Individual Are Highlighted
Keywords: Professionalism; Creative-Communicative Ability; CreativeCommunicative; Creativeness; Intellektual Level